The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/jmv.21275
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 diversity among inmates of Italian prisons

Abstract: In Italy, the prevalence of non-B HIV-1 subtypes ranges reportedly from 5.4% to 12.6%, yet there are no data on their circulation in prisons, where the prevalence of HIV infection is high. A retrospective study was conducted to evaluate the circulation of non-B subtypes and to characterize their determinants in five Italian prisons. To this end an aliquot of samples of blood was taken in the period 2001-2006 from all 262 HIV-positive inmates in whom antiretroviral treatment had failed. Complete HIV-1 PR and RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Prevalence of HIV subtypes in prison is strongly influenced by the frequency of foreign people in each prison. [ 13 ] As well, prevalence of HCV genotypes may be influenced by the route of infection and coinfection, regardless of the geographic variable, and may differ between risk groups and the general population. [ 14 ] Knowledge of the prevalence of different subtypes of HIV, HBV, and HCV circulating in prisons may be useful to track the epidemiology of infection and choose appropriate therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of HIV subtypes in prison is strongly influenced by the frequency of foreign people in each prison. [ 13 ] As well, prevalence of HCV genotypes may be influenced by the route of infection and coinfection, regardless of the geographic variable, and may differ between risk groups and the general population. [ 14 ] Knowledge of the prevalence of different subtypes of HIV, HBV, and HCV circulating in prisons may be useful to track the epidemiology of infection and choose appropriate therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV strains phylogenetic analysis showed that the majority of inmates of Italian nationality were infected with the HIV-1 subtype B, except two, one infected with the recombinant form CRF72_BF1, and the other one with the HIV-1 sub-subtype A6, both previously not identified in inmates of Italian nationality 30 , 31 . CRF72_BF1 was isolated in Brazil 32 , and it has spread in Spain.…”
Section: Discussionmentioning
confidence: 90%